The Vibrio type VI secretion system induces intestinal macrophage redistribution and enhanced intestinal motility - Julia S. Ngo; Piyush Amitabh; Jonah G. Sokoloff; Calvin Trinh; Travis J. Wiles; Karen Guillemin; Raghuveer Parthasarathy (mBio)
ABSTRACT Intestinal microbes, whether resident or transient, influence the physiology of their hosts, altering both the chemical and the physical characteristics of the gut. An example of the latter is the human pathogen Vibrio cholerae’s ability to induce strong mechanical contractions, discovered in zebrafish. The underlying mechanism has remained unknown, but the phenomenon requires the actin crosslinking domain (ACD) of Vibrio’s type VI secretion system (T6SS), a multicomponent protein syringe that pierces adjacent cells and delivers toxins. By using a zebrafish-native Vibrio and imaging-based assays of host intestinal mechanics and immune responses, we find evidence that macrophages mediate the connection between the T6SS ACD and intestinal activity. Inoculation with Vibrio gives rise to strong, ACD-dependent, gut contractions whose magnitude resembles those resulting from genetic depletion of macrophages. Vibrio also induces tissue damage and macrophage activation, both ACD-dependent, recruiting macrophages to the site of tissue damage and away from their unperturbed positions near enteric neurons that line the midgut and regulate intestinal motility. Given known crosstalk between macrophages and enteric neurons, our observations suggest that macrophage redistribution forms a key link between Vibrio activity and intestinal motility. In addition to illuminating host-directed actions of the widespread T6SS protein apparatus, our findings highlight how localized bacteria-induced injury can reshape neuro-immune cellular dynamics to impact whole-organ physiology.IMPORTANCEGut microbes, whether beneficial, harmful, or neutral, can have dramatic effects on host activities. The human pathogen Vibrio cholerae can induce strong intestinal contractions, though how this is achieved has remained a mystery. Using a zebrafish-native Vibrio and live imaging of larval fish, we find evidence that immune cells mediate the connection between bacteria and host mechanics. A piece of Vibrio’s type VI secretion system, a syringe-like apparatus that stabs cellular targets, induces localized tissue damage, activating macrophages and drawing them from their normal residence near neurons, whose stimulation of gut contractions they dampen, to the damage site. Our observations reveal a mechanism in which cellular rearrangements, rather than bespoke biochemical signaling, drives a dynamic neuro-immune response to bacterial activity.